ANALISIS YURIDIS TERHADAP KEWENANGAN DIREKTORAT JENDERAL PAJAK ATAS PENAGIHAN HUTANG PAJAK WAJIB PAJAK YANG PAILIT (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 759 K / PDT.SUS-PAILIT/ 2016) - HARIYANI HARIYANI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Utary Maharany Barus3. Bastari The rights of the Directorate General of Taxes over tax arrears collection to a taxpayer who has been declared to be bankrupt are frequently ignored. In fact, it is one of the revenues of the country which is used for the benefit of the society. There is a legal phenomenon related to such thing found in the case No.759 K/Pdt.Sus-Pailit/2016 in which the authority and rights of the Directorate General of Taxes are restored after they were lost due to the Court Ruling No. 3/G.lain-lain/2016/PN.Niaga.Surabaya. The research problems are about the authority and rights of the Directorate General of Taxes are over the tax arrears collection to PT. Tiga Daratan which has been declared to be bankrupt, about the fulfillment of legal certainty principle in the Ruling of the Supreme Court No. 759 K/Pdt.Sus-Pailit/2016, and about the legal consequence of the Ruling of the Supreme Court No. 759 K/Pdt.Sus-Pailit/2016. Keywords: Directorate General of Taxes, Collection of Tax Arrears, and Bankrupt